An Underwater Acoustic Implementation of DFT-Spread OFDM. (14th February 2010) - Zhang Zhang, Yonghuai Yonghuai; Sun Sun, Haixin Haixin; Cheng Cheng, En En; Shen Shen, Weijie Weijie
Abstract : This paper presents a design of DFT-spread OFDM system applied to an underwater acoustic channel. It does not only combine all the advantages of a conventional OFDM system but also reduces the peak-to-average power ratio of the transmit signal. Besides, the scheme spreads the information over several subcarriers as a result of the application of an additional DFT operation and leads to a diversity gain in a frequency-selective fading channel, which is one of the many challenges of communicating data through an underwater acoustic channel. Simulation results show that our proposal possesses good bit-error-rate performance. The system has been tested in a real underwater acoustic channel—the experimental pool in Xiamen University. The experimental results show that the DFT-spread OFDM system can achieve better results than a simple OFDM system in a benign underwater channel.